School and coloniality. Variants and (aesthetic) invariants of social classification. DOI: 10.37785/nw.v3n2.a7 - Giuliano, Facundo (Nawi, 2019)
One of the first space-times, if not the first, where corporalities are judged, examined, evaluated and, therefore, classified, is probably the school. At least since the 19th century, in non-European latitudes, it is institutionally consolidated within the different educational systems as an apparatus of uninterrupted examination that classifies bodies and produces subjectivities according to the governmental requirements of the time. Of course, the school experiences, hegemonic and counter-hegemonic, are and have been innumerable but this does not detract from the fact of thinking about the persistence of this institution so criticized and so newly defended within the framework of the processes of re-westernization and re-strengthening of the colonial power matrix. In this sense, our concern is to investigate the place of the evaluative reason and the classificatory aesthetics in the new discourses of defense or vindication of the school at the same time that we try to make some guidelines for a decolonization of the scholé.
Keywords: decoloniality, scholé, evaluative reason, education, geopolitics